Low-voltage high-speed PWM signal generations based on relaxation oscillator - Siripruchyanun, M.; Wardkein, P. (My University, 2002)
This paper new two simple PWM (pulse width modulation) signal generations based on a modified relaxation oscillator are introduced. The advantages of the proposed principle are that the precise PWM signal can be easily achieved with a high frequency range up to several megahertz and a low-voltage power supply. The proposed circuits are able to accept either voltage or current modulating signals. They are very suitable for developing into integrated circuit (IC) form in communication applications. The simulation and experimental results are also depicted, and show good agreement with theoretical predictions.
Keywords: Application specific integrated circuits; Frequency; Oscillators; Power supplies; Pulse generation; Pulse width modulation; Pulsed power supplies; Signal generators; Space vector pulse width modulation; Voltage